Penetapan Kadar Inulin dalam Ekstrak Umbi Dahlia variabilis dan Dahlia pinnata dengan Metode KLT Densitometri (Determination of Inulin Content in Dahlia variabilis and Dahlia pinnata Tuber Extract by TLC Densitometry Method) - Khoirun Nisa'; Yuni Retnaningtyas; Nia Kristiningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Inulin is a polymer which have many benefits for health and used widely for food. The absence of research on determination of inulin content in dahlia tuber extract from different species, made this study very important to do. The purpose of this study was to determine the inulin content in dahlia tuber extract from different species. So it can be known the most effective type of dahlia to be the major source of inulin production. The method used in this study was TLC densitometry. The result showed that the inulin content in Dahlia variabilis tuber extract was 73.93 ± 1.209%, and the inulin content in Dahlia pinnata tuber extract was 66.76 ± 0.572%. The inulin content in Dahlia variabilis and Dahlia pinnata tuber extract were significantly different. Keywords: inulin, dahlia tuber, Dahlia variabilis, Dahlia pinnata, TLC densitometry